Pengaruh Green Product dan Green Marketing terhadap Minat Beli Ulang (Studi Kasus Konsumen Starbucks di Tembung) - Amaliyah, Amaliyah; Amelia, Wan Rizca; Alfifto, Alfifto (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the influence of green products and green marketing on repeat purchase intention (case study of Starbucks consumers in Tembung). A quantitative approach is used to determine the magnitude of the influence of independent variables on dependent variables. The population in this study is Starbucks in Tembung, where the number is unknown. Because the number of Starbucks customers in Tembung is unknown, the sample size was determined using a formula based on Malhotra's theory. Istiyawari et al (2021) state that Malhotra's formula is to multiply by 4 or 5 times the number of indicators, so 22 x 5 = 110 respondents. Data analysis was performed using SPSS 27 with multiple linear regression to determine the effect of independent variables on dependent variables. The results showed that the Green Product variable had a positive and significant effect on repurchase intention. This can be seen from the significance value (0.000) < 0.05 and the t-count (6.612) > the t-table (1.982). The Green Marketing variable has a positive and significant effect on Repurchase Intention. This can be seen from the significant value (0.000) < 0.05 and t-count (6.377) > compared to t-table (1.982). Simultaneously, Green Product (X1) and Green Marketing (X2) are both significant for Repurchase Intention.